To Investigate the Barriers to Participation of Female on Recreational Sports Activities - Manzoor, Mehwish; Aman, Reema; Mahreen, Sadia (Annals of Human and Social Sciences, 2023)
The main purpose of this study was to investigate barriers to participation Female on recreational-sportive activities. The sample of this study consisted of 300 Female from district 8 that selected through simple random sampling among 188617 females. The questionnaire that used at this study was Physical Activity Participation Barriers in which consisted of 22 items. The method of the study is descriptive correlational. The data was collected using questionnaires and through field study procedure. Descriptive statistics were used for describing and categorizing raw data and for measuring Mean, frequency, SD and table drawing. Also, KMO and exploratory factor analysis by using T-Value and also One- sample T analysis was used. For analyzing data, the SPSS and LISSREL software was applied. The results of this study indicate that barriers to participation are include structural and transportation, intrapersonal, family and abilities, timing and facilities, cultural, physical and psychological barriers.